International student mobility to non-traditional destination countries: evidence from a host country - Apsite-BerinaElina; RobateLiga Daniela; Berzins, Maris; Burgmanis, Girts; Krisjane, Zaiga (Hungarian Geographical Bulletin, 2023)
Since the early 1990s, Latvia has experienced high levels of emigration. Still, current dynamics show that net migration has nearly ceased and that a growing share of new immigrant populations are from non-European countries. One of the leading causes of a sizable share of recent immigration is the globalisation of higher education and the mobility of international students. However, in recent decades, international student mobility (ISM) has brought attention to various aspects of higher education, educational export, and migration trends. This has captured the interest of academics and practitioners worldwide. Receiving countries recognise the importance of attracting international students as potential residents, especially as they undergo unfavourable demographic changes. The paper aims to present empirical evidence on ISM in Latvia by assessing international student daily life and study experiences. The focus is on examining the perspective of a host country. The study utilises statistical data, survey data and a case study of the University of Latvia to analyse the link between the origin of the student and their choosing Latvia as a non-traditional destination for quality higher education. The findings indicate that Latvia is an attractive destination for young migrants from diverse geographies, including Europe and Southeast Asia and consistent flows of students from former Soviet countries. One of the main factors that draw international students to Latvia is the affordability of education offered in English, providing a “second chance” for achieving success and specific clusters of degree students from European countries studying medicine.